Current state of the problem of exfoliative dermatitis - L. A. Yusupova (Лечащий Врач)
The article presents data on exfoliative dermatitis, characterized by diffuse erythema and skin peeling, affecting more than 90% of the total body surface. The most common diseases, previous to exfoliative dermatitis, are psoriasis, atopic dermatitis and other spongiotic dermatitis, drug hypersensitivity reaction (drug toxicodermia) and cutaneous T-cell lymphoma. The treatment is directed at the primary disease, symptomatic relief and prevention of potential systemic complications.